Une étude du rapport au savoir d’enfants scolarisés en IME dans le cadre d’un parcours artistique - Céline Salles; Florence Savournin (Recherches en Éducation)
Teaching in a Medical Educational Institute demands that the teacher takes into account the special educational needs of each pupil. The Learning process and more specifically the language is affected by the limited symbolique capacities in children with intellectual disability. These children can manifest typical behaviour such as incapability, refusal, retreat or docility when faced with educational demands. Setting up an artistic and cultural based ‘Learning journey’, adapted to their needs, allows observation and analysis of the adjustments needed in the relation to knowledge of three young children.